High-strength glass-ceramics and method for enhancing intrinsic and bulk strength of glass-ceramics by fractional crystallization and ion exchange
Patent Information
- Application Number
- CN202611286564.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-24
- Publication Date
- 2026-10-16
AI Technical Summary
微晶玻璃的离子交换主要发生在残余玻璃相中,对于晶体组成含碱金属离子的微晶玻璃(即第一类),随着晶体含量的升高残余玻璃相中碱金属离子的相对含量下降,导致离子交换性能降低
(1)本发明制得的高强度微晶玻璃实现了Mg2SiO4晶体与NaAlSiO4晶体在玻璃基体中的共存,二者并非简单复合,而是通过合理的组成设计与热处理工艺控制,实现了有序析晶。具体而言,在较低温度或较短时间下优先析出Mg2SiO4晶体,随后在较高温度或较长时间下进一步析出NaAlSiO4晶体。该有序析晶过程能够有效调控NaAlSiO4晶体的生长,进而控制其含量,从而调节残余玻璃相中的Na+离子浓度,最终实现对离子交换性能的灵活调控,确保微晶玻璃的本体及整体强度、离子交换性能协同提升。若未采用该有序析晶方法,NaAlSiO4的析晶将失去控制,难以有效调控其含量,显著削弱离子交换效果,不利于微晶玻璃整体性能的优化。
Smart Images

Figure CN122916441A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of inorganic non-metallic materials technology, specifically to a high-strength glass-ceramic and a method for enhancing the intrinsic and overall strength of the glass-ceramic using stepwise crystallization and ion exchange. Background Technology
[0002] The drop and scratch resistance of smartphones are key factors affecting their reliability and lifespan. As an important protective component, the back panel material plays a crucial role in the overall safety of the phone. In recent years, with the widespread adoption of technologies such as 5G communication and wireless charging, smartphone back panel materials have gradually shifted from traditional metallic materials to non-metallic materials. Among these, microcrystalline glass, due to its excellent mechanical properties, shows significant application potential in the field of smartphone back panels.
[0003] As a protective material, glass-ceramics typically require chemical strengthening (i.e., ion exchange) before use to further enhance their strength. Ion exchange usually utilizes larger alkali metal ions in molten salt to replace smaller alkali metal ions in the glass-ceramic, forming a compressive stress layer of a certain depth on the surface through a "squeezing effect," thereby effectively enhancing the strength of the glass-ceramic. Ion exchange in glass-ceramics is mainly divided into two categories: one is K... + -Na + Exchange, that is, utilizing K in molten salt + Replace Na in glass-ceramics + Another type is Na. + -Li + Exchange, that is, utilizing the Na in molten salt + Li replacing microcrystalline glass + For the former, due to K + with Na + The ionic radii differ significantly, and after exchange, high compressive stress can be generated on the surface, thereby significantly improving the strength of the glass-ceramic. However, K + The larger radius results in a lower diffusion rate of K within the glass matrix. + -Na + The ion exchange layer is relatively shallow. In contrast, Na + -Li + Ion exchange can achieve deeper exchange layers, but with lower surface compressive stress. To optimize the ion exchange performance of glass-ceramics, it is generally desirable to obtain deeper Kc layers. + -Na + Exchange layer. However, the presence of crystalline phases in glass-ceramics inhibits the diffusion of alkali metal ions, especially those with larger K ions. + The obstacles are more significant, often leading to K + -Na + The exchange layer depth is insufficient. Therefore, how to effectively increase the K content in glass-ceramics is a key issue.+ -Na + Ion exchange depth has become an important problem that urgently needs to be solved in this field.
[0004] Based on their crystal composition, glass-ceramics can be divided into two main categories: one containing alkali metal ions, such as sodium nepheline (NaAlSiO4), lithium nepheline (LiAlSiO4), and lithium disilicate (Li2Si2O5); and the other without alkali metal ions, such as spinel (MgAl2O4), olivine (Mg2SiO4), and zinc silicate (Zn2SiO4). Different crystal types endow glass-ceramics with different ion exchange properties. Ion exchange in glass-ceramics mainly occurs in the residual glass phase. For glass-ceramics with alkali metal ions in their crystal composition (i.e., the first type), as the crystal content increases, the relative content of alkali metal ions in the residual glass phase decreases, leading to a decrease in ion exchange performance. For glass-ceramics without alkali metal ions in their crystal composition (i.e., the second type), an increase in crystal content increases the relative content of alkali metal ions in the residual glass phase, while divalent metal ions (such as Mg...)... 2+ Ca 2+ Zn 2+ The precipitation of alkali metal ions can broaden the glass network channels, further promoting the diffusion of alkali metal ions and thus enhancing ion exchange performance. In summary, the precipitation of crystals that do not contain alkali metal ions is beneficial to the ion exchange process of glass-ceramics.
[0005] The total strength of glass-ceramics consists of two parts: bulk (or intrinsic) strength and ion exchange strength. Ion exchange strength enhances surface strength through surface compressive stress and induces surface crack deflection, thereby improving the material's strength and toughness. Bulk strength, on the other hand, ensures that the material maintains sufficient residual strength even after a crack penetrates the compressive stress layer. From a compositional design perspective, glass-ceramics with excellent mechanical properties require both high bulk strength and high ion exchange strength. The former typically requires a low alkali metal content in the composition to reduce its destructive effect on the glass network structure, while the latter requires a high alkali metal ion content to ensure good ion exchange capacity. Therefore, achieving a balance between bulk strength and ion exchange strength has become a key issue that urgently needs to be addressed in current glass-ceramic research. Summary of the Invention
[0006] The main objective of this invention is to resolve the inherent contradiction between the bulk strength and ion exchange performance of glass-ceramics, providing a high-strength glass-ceramic and a method for enhancing its intrinsic and overall strength through stepwise crystallization and ion exchange. This method involves the sequential precipitation of Mg₂SiO₄ and NaAlSiO₄ crystals within the glass-ceramic. The precipitation of Mg₂SiO₄ promotes the improvement of the bulk and overall strength and ion exchange performance of the glass-ceramic, while the precipitation of NaAlSiO₄ consumes excess Na₂SiO₄ in the residual glass phase. + This reduces the destructive effect on the glass network structure and further enhances the bulk and overall strength of the glass-ceramic. Through the synergistic effect of two different crystals, this invention effectively balances the bulk and overall mechanical properties and chemical strengthening capabilities of the glass-ceramic, ultimately producing a high-performance glass-ceramic product.
[0007] As one aspect of the present invention, the present invention provides a high-strength microcrystalline glass. The high-strength microcrystalline glass comprises a glass phase and crystals dispersed in the glass phase, wherein the crystals include crystal A which does not contain alkali metal ions and crystal B which contains alkali metal ions.
[0008] In the above scheme, crystal A is specifically Mg2SiO4 crystal, and crystal B is specifically NaAlSiO4 crystal.
[0009] In the above scheme, crystal A precipitates before crystal B in the high-strength microcrystalline glass, and the contents of the two crystals are equal or unequal.
[0010] In the above scheme, the raw materials of the high-strength microcrystalline glass, by molar percentage, include: SiO2 39.7%-45.5%, MgO 31.7%-36.8%, Al2O 38.3%-14.4%, Li2O 0%-1.5%, Na2O 4.7%-8.4%, K2O 0%-1%, TiO2 3.2%-4.9%, ZrO2 0%-1%, Y2O 30%-1.5%, wherein 75.3%≤MgO+SiO2≤78.5%, 0.72≤MgO / SiO2≤1, and 0.37≤Na2O / Al2O3≤1.02.
[0011] As a preferred embodiment, the high-strength microcrystalline glass comprises the following raw materials by molar percentage: SiO2 39.7%-42.8%, MgO 34.4%-36.8%, Al2O3 11%-14.4%, Na2O 5.4%-7.6%, K2O 0%-0.5%, TiO2 3.5%-4.7%, ZrO2 0%-0.5%, and Y2O3 0%-0.5%, wherein 76.2%≤MgO+SiO2≤77.8%, 0.78≤MgO / SiO2≤0.92, and 0.42≤Na2O / Al2O3≤0.69.
[0012] In the above scheme, the Vickers hardness of the high-strength microcrystalline glass is not less than 7.8 GPa, preferably 7.8 GPa-10.8 GPa, and more preferably 9.0 GPa-10.8 GPa.
[0013] As another aspect of the present invention, the present invention also provides a method for enhancing the intrinsic strength and overall strength of glass-ceramics by using stepwise crystallization and ion exchange (i.e., the above-mentioned method for preparing high-strength glass-ceramics), the method comprising: preparing a base glass, subjecting the base glass to heat treatment to induce the sequential precipitation of Mg2SiO4 crystals and NaAlSiO4 crystals, followed by ion exchange, and finally obtaining the desired high-strength glass-ceramics.
[0014] In the above scheme, the preparation method of the base glass includes: mixing the base glass raw materials according to the aforementioned ratio, then heating to 1500℃-1600℃ to completely melt it, and after the molten glass material is formed, annealing it at 600℃-650℃ to obtain the base glass.
[0015] In the above scheme, the base glass is heat-treated using a one-step or two-step method. The one-step heat treatment specifically involves placing the base glass at 750℃-950℃ for 5-10 hours; the two-step heat treatment specifically involves placing the base glass at 700℃-750℃ for 5-10 hours in the first step, and then transferring it to 800-950℃ for another 5-10 hours of heat treatment.
[0016] In the above scheme, the base glass is heat-treated at 850℃-900℃ for 10 hours, or first heat-treated at 750℃ for 10 hours and then transferred to 850℃ for 5-10 hours. During the heat treatment process, Mg2SiO4 crystals and NaAlSiO4 crystals precipitate successively, resulting in a Vickers hardness of 7.8GPa-10.0GPa for the microcrystalline glass.
[0017] In the above scheme, the ion exchange specifically refers to K + -Na +Ion exchange was performed using KNO3 as the molten salt, at a temperature of 440℃-500℃, for a time of 2-10 hours, resulting in an ion exchange layer depth of 5μm-85μm. The Vickers hardness of the resulting glass-ceramic was enhanced to 9.1-10.8 GPa.
[0018] The increased strength of the high-strength glass-ceramic in this invention stems from the synergistic enhancement of both the bulk strength and ion exchange performance of the glass-ceramic, ultimately improving its overall strength. Specifically, this invention first preferentially precipitates Mg₂SiO₄ crystals within the glass through the composition design and heat treatment process of the base glass. The precipitation of Mg₂SiO₄ crystals not only contributes to improving the bulk strength of the glass-ceramic but also promotes the ion exchange process, particularly K₂SiO₄. + -Na + Ion exchange works through the following three mechanisms: Firstly, Mg2SiO4 itself has high mechanical properties, such as elastic modulus (about 185 GPa) and hardness (about 10.8 GPa). Therefore, the precipitation of Mg2SiO4 crystals is beneficial to improving the bulk strength of glass-ceramics.
[0019] Secondly, Mg in glass 2+ Due to its high electric field strength and weak mobility, it typically blocks glass network channels, hindering the diffusion of alkali metal ions and impeding ion exchange. Furthermore, with the crystallization of Mg₂SiO₄, the Mg in the residual glass phase... 2+ As the concentration decreases, its "blocking effect" on the network channels weakens, thus promoting ion exchange.
[0020] Third, Mg2SiO4 crystals do not contain alkali metal ions, and the residual glass phase after crystallization still maintains a high content of alkali metal ions, which is beneficial to improving ion exchange performance. However, although the high content of alkali metal ions in the residual glass phase is beneficial to ion exchange, it will damage the glass network structure and affect the bulk strength of the glass-ceramic.
[0021] To balance the bulk strength and ion exchange performance of glass-ceramics, this invention innovatively proposes to further precipitate NaAlSiO4 crystals on top of Mg2SiO4 crystals, thereby reducing excessive alkali metal ions in the residual glass phase. The content of NaAlSiO4 crystals can be controlled through preferential crystallization of Mg2SiO4 and heat treatment processes, thereby optimizing ion exchange performance and ultimately promoting the overall strength improvement of the glass-ceramics.
[0022] To achieve the controllable precipitation of Mg2SiO4 and NaAlSiO4 crystals in glass, it is essential to ensure that the original glass has good glass-forming properties (i.e., glass-forming ability). Therefore, the control of composition is crucial.
[0023] In this invention, the contents of SiO2 and MgO have a significant impact on the crystallization of Mg2SiO4 and require precise control. SiO2 is a glass network forgery and also the source of Si in forsterite crystals. When the SiO2 content is low, it is not conducive to the crystallization of Mg2SiO4 and will lead to poor glass stability and low glass-forming properties; while excessively high SiO2 content will result in a high glass melt viscosity and increased melting difficulty. Therefore, through a series of experimental studies and theoretical analyses, this invention ultimately determined that the suitable SiO2 content is 39.7%-45.5%.
[0024] In this invention, MgO is a key raw material for the formation of Mg2SiO4, and its content directly affects the crystallization ability of Mg2SiO4. Furthermore, MgO is also the outer layer of the glass network, thus influencing glass formation properties. When the MgO content is low, Mg2SiO4 is difficult to crystallize; when the MgO content is high, it has a greater destructive effect on the glass network, reducing glass stability and worsening glass formation properties. Therefore, through a series of experimental studies and theoretical analyses, this invention ultimately determined that the suitable MgO content range is 31.7%-36.8%.
[0025] On the other hand, to ensure the preferential precipitation of Mg2SiO4 in the glass, the total amount of MgO and SiO2 must also be limited. Specifically, the sum of their contents must be controlled between 75.3% and 78.5% (i.e., 75.3% ≤ MgO + SiO2 ≤ 78.5%). If the total amount of MgO and SiO2 is too low, Mg2SiO4 will be difficult to crystallize; if the total amount is too high, it will lead to a relative decrease in the content of other oxides, which is not conducive to improving the overall performance of the glass-ceramic (such as nucleation performance, ion exchange performance, etc.). In addition, the ratio of MgO to SiO2 is also limited (0.72 ≤ MgO / SiO2 ≤ 1). If the ratio of MgO to SiO2 is too low, Mg2SiO4 will be difficult to crystallize, while if the ratio is too high, the stability of the glass will deteriorate.
[0026] In this invention, Al2O3 serves as an intermediate in the glass network and significantly influences the formation of the NaAlSiO4 crystal phase and its ion exchange performance. When the Al2O3 content is too low, it hinders the precipitation of NaAlSiO4 crystals and ion exchange; when the Al2O3 content is too high, glass melting becomes difficult, product quality is poor, and stone formation is likely during the melting process, resulting in low economic efficiency. Taking all factors into consideration, the Al2O3 content range determined in this invention is 8.3%-14.4%.
[0027] In this invention, Na₂O serves as a network modifier and is a necessary component for the formation of the NaAlSiO₄ crystalline phase, as well as a key element required for ion exchange. The amount of Na₂O directly affects the crystallization of NaAlSiO₄ and the ion exchange performance of the glass. When its content is too low, NaAlSiO₄ is difficult to precipitate, and the ion exchange effect is poor; the higher the Na₂O content, the worse the chemical stability of the glass, leading to a decrease in mechanical properties. After comprehensive consideration, the Na₂O content determined in this invention is 4.7%-8.4%.
[0028] Furthermore, the crystallization of NaAlSiO4 is also related to the relative contents of Na2O and Al2O3 in the glass composition. The ratio of the two should be limited to 0.37 ≤ Na2O / Al2O3 ≤ 1.02. If this ratio is too low, not only will NaAlSiO4 be difficult to precipitate, but it will also be detrimental to the ion exchange of the glass-ceramic; if this ratio is too high, the alkali metal content in the residual glass phase will be too high, which is not conducive to improving the bulk strength of the glass-ceramic.
[0029] In this invention, Li₂O and Na₂O serve similar functions, both acting as network modifiers that can lower the glass melting temperature and regulate crystallization behavior. When the Li₂O content is too high, the glass is prone to developing impurities such as quartz solid solution after heat treatment, ultimately leading to glass cracking. Taking all factors into consideration, the Li₂O content determined in this invention is 0%-1.5%.
[0030] This invention may also contain a certain amount of Y₂O₃, whose main function is to enhance the mechanical properties of the glass-ceramic to a certain extent by accumulating rare earth ions in the glass network through the high field strength, and to suppress crystallization during the glass casting process. The content of Y₂O₃ should not be too high, as excessive content can easily lead to phase separation in the glass, block the glass network channels, and affect ion exchange. After comprehensive consideration, the Y₂O₃ content determined in this invention is 0%-1.5%.
[0031] In this invention, TiO2 and ZrO2 serve as nucleating agents, playing a crucial role in glass nucleation and crystallization. TiO2 is selected as the primary nucleating agent, and ZrO2 as an auxiliary nucleating agent, the latter of which can be added in small amounts. Excessive ZrO2 content hinders the precipitation of forsterite, leading to a decrease in the mechanical properties of the glass. Conversely, excessive nucleating agent content can increase crystallization during glass casting, reducing glass formation. Considering all factors, this invention determines the TiO2 content to be 3.2%-4.9% and the ZrO2 content to be 0%-1%.
[0032] Compared with existing similar products or technologies, the advantages or beneficial effects of this invention are mainly reflected in the following aspects: (1) The high-strength microcrystalline glass prepared by this invention achieves the coexistence of Mg2SiO4 crystals and NaAlSiO4 crystals in the glass matrix. The two are not simply composites, but rather, through rational composition design and controlled heat treatment processes, ordered crystallization is achieved. Specifically, Mg2SiO4 crystals preferentially precipitate at lower temperatures or shorter times, followed by further precipitation of NaAlSiO4 crystals at higher temperatures or longer times. This ordered crystallization process effectively regulates the growth of NaAlSiO4 crystals, thereby controlling their content and adjusting the Na content in the residual glass phase. + The ion concentration ultimately enables flexible control of ion exchange performance, ensuring a synergistic improvement in the bulk and overall strength and ion exchange performance of the glass-ceramic. Without this ordered crystallization method, the crystallization of NaAlSiO4 becomes uncontrollable, making it difficult to effectively regulate its content, significantly weakening the ion exchange effect, and hindering the optimization of the overall performance of the glass-ceramic.
[0033] (2) The high-strength glass-ceramics prepared by this invention balance bulk strength, overall strength, and ion exchange performance, all of which can be autonomously controlled through basic component design and heat treatment processes. The improvement in bulk strength and overall strength stems from the precipitation of high-strength Mg2SiO4 crystals and benefits from the enhanced residual glass phase network structure resulting from NaAlSiO4 crystallization. Ion exchange performance can be optimized by adjusting the NaAlSiO4 crystal content while meeting bulk strength requirements. Ultimately, this invention achieves a good balance between bulk strength and ion exchange performance in glass-ceramics.
[0034] (3) The high-strength microcrystalline glass prepared by this invention has excellent K + -Na + The ion exchange performance is excellent, and the depth of the ion exchange layer can be flexibly adjusted within a wide range (5μm-85μm). This wide depth control capability is due to the effective control of the NaAlSiO4 crystal content: when its content is high, the Na in the residual glass phase... + A lower NaAlSiO4 content results in a shallower ion exchange layer; conversely, a lower NaAlSiO4 content leads to a higher Na content in the residual glass phase. + As the content increases, the ion exchange layer deepens. Therefore, this invention allows for flexible adjustment of ion exchange performance to meet the needs of different application scenarios and differentiated requirements. Attached Figure Description
[0035] Figure 1 The images are XRD patterns of the glass composition described in Example 8 after heat treatment under different conditions.
[0036] Figure 2 The XRD patterns are of the glass composition described in Example 10 after heat treatment under different conditions.
[0037] Figure 3 The image shows a TEM image of a glass-ceramic formed by heat-treating the glass composition described in Example 1 at 800°C for 10 hours.
[0038] Figure 4 The image shows a TEM image of a glass-ceramic formed by heat-treating the glass composition described in Example 1 at 900°C for 10 hours.
[0039] Figure 5 The microcrystalline glass formed by heat treatment under different conditions according to the composition of Example 8, after ion exchange at 480°C / 8h, K + Concentration distribution curve.
[0040] Figure 6 The microcrystalline glass formed by heat treatment under different conditions according to the composition of Example 10, after ion exchange at 480°C / 8h, K + Concentration distribution curve.
[0041] Figure 7 The Vickers hardness diagrams are shown for the microcrystalline glass formed by heat treatment under different conditions before and after ion exchange, based on the glass composition described in Example 8.
[0042] Figure 8 The Vickers hardness diagrams are of the microcrystalline glass formed by heat treatment under different conditions of the glass composition described in Example 10 before and after ion exchange. Detailed Implementation
[0043] To enable those skilled in the art to fully understand the technical solution and beneficial effects of the present invention, further detailed description is provided below in conjunction with specific embodiments and accompanying drawings. It should be emphasized that the embodiments listed below are merely preferred embodiments of the present invention and do not constitute a limitation thereof. Any simple improvements made based on these embodiments will fall within the protection scope of the present invention.
[0044] To avoid obscuring the invention with unnecessary details, the following embodiments only show the raw materials, methods, and steps closely related to the technical solutions of the invention, while omitting some other conventional details. The term "comprising / including" in the invention indicates the presence of features, elements, steps, etc., but does not exclude the presence or addition of one or more other features, elements, steps.
[0045] Unless otherwise specified, all raw materials mentioned in this invention are commercially available, and all units of measurement are international units.
[0046] The specific methods for preparing the glass-ceramic samples in Examples 1-13 and Comparative Examples 1-7 of this invention are as follows: The first step is to accurately prepare the raw materials and proportions according to the design. After mixing the raw materials evenly, heat them to 1600℃ and keep them at this temperature for 2 hours. After the raw materials are completely melted, clarified and homogenized, molten glass material is obtained. The second step is to pour the molten glass into a mold to form a shape, and then transfer it to an annealing furnace to anneal at 600°C for 5 hours to obtain the original glass sheet.
[0047] The third step involves heat-treating the glass sheet using a one-step or two-step method, followed by cutting and polishing.
[0048] The fourth step involves ion exchange of the polished glass slide to obtain the desired high-strength glass-ceramic. The specific ion exchange process is as follows: KNO3 molten salt is placed in a tempering furnace and heated to 480℃ to completely melt the salt. The glass slide is then preheated to the same temperature as the molten salt and immersed in the KNO3 molten salt for 8 hours. After removal, it is allowed to cool naturally to room temperature and then cleaned with deionized water to obtain the desired ion-exchanged high-strength glass-ceramic sample.
[0049] To fully understand the impact of the third-step heat treatment conditions on the composition and properties of glass-ceramics, two sets of control experiments (heat treatment group A and heat treatment group B) were conducted on samples of each formulation under different heat treatment temperatures and times.
[0050] The specific process parameters for Examples 1-13 are shown in Table 1-2 below.
[0051] Table 1. Comparison of formulations and parameters for Examples 1-7
[0052] Table 2. Comparison of formulations and parameters for Examples 8-13
[0053] Examples 1-13 achieved the technical effect of precipitating Mg2SiO4 crystals through low-temperature or short-time heat treatment and precipitating NaAlSiO4 crystals through high-temperature or long-time heat treatment by rational control of the components. Finally, high-strength microcrystalline glass containing Mg2SiO4 crystals and NaAlSiO4 crystals was obtained, and efficient ion exchange was achieved.
[0054] As can be seen from Examples 1-7 in Table 1, lower temperature heat treatment (800℃) can achieve crystallization of Mg2SiO4, while higher temperature heat treatment (850 or 900℃) can achieve co-crystallization of Mg2SiO4 and NaAlSiO4. When only Mg2SiO4 crystallizes, the Vickers hardness of the glass-ceramic is between 7.4 and 8.3 GPa. After K... + -Na +After ion exchange, the Vickers hardness of the glass-ceramic increased significantly, and the ion exchange layer depth was between 60-80 μm. These results demonstrate that the individual crystallization of Mg₂SiO₄ can achieve efficient K₂O₃ crystallization. + -Na + Ion exchange. When Mg₂SiO₄ and NaAlSiO₄ co-precipitate, the Vickers hardness of the glass-ceramic is further improved (compared to glass-ceramics with only Mg₂SiO₄ precipitation), thus proving that NaAlSiO₄ precipitation is beneficial to improving the bulk strength of the glass-ceramic. Furthermore, this glass-ceramic undergoes K... + -Na + After ion exchange, the Vickers hardness was further improved; however, the depth of the ion exchange layer was significantly reduced. This indicates that although the crystallization of NaAlSiO4 can improve the bulk strength of the glass-ceramic, it reduces the ion exchange performance.
[0055] Table 2 shows the results of Examples 8-10 with the same basic composition under different heat treatment conditions. As can be seen from the table, when heat-treated at 750 or 800℃ for 10 hours or at 850℃ for 5 hours, only Mg2SiO4 crystals precipitate; when heat-treated at 850℃ for 10 hours or first at 750℃ for 10 hours followed by 850℃ for 5-10 hours, both Mg2SiO4 and NaAlSiO4 crystals precipitate. Similar to the pattern observed in Examples 1-7 of Table 1, the crystallization of NaAlSiO4 further increases the Vickers hardness of the glass, but also leads to a decrease in the depth of the ion exchange layer.
[0056] For Example 9, when the heat treatment conditions were 850℃ / 5h, only Mg2SiO4 precipitated. Comparing this sample with the sample heat-treated at 850℃ / 10h in Example 8, it can be seen that only Mg2SiO4 crystals precipitated when the heat treatment time was shorter, while extending the heat treatment time could achieve co-precipitation of Mg2SiO4 and NaAlSiO4.
[0057] For Example 9, only Mg2SiO4 precipitated when the heat treatment condition was 750℃ / 10h. Comparing this sample with the sample heat-treated at 800℃ / 10h in Example 8, it can be seen that both the Vickers hardness and ion exchange depth are reduced, mainly due to the lower Mg2SiO4 crystal content under this condition (750℃ / 10h). This result further illustrates that the crystallization of Mg2SiO4 not only improves the bulk strength of the glass-ceramic but also promotes its ion exchange performance.
[0058] Example 10 illustrates the performance of the glass-ceramic after a two-step heat treatment. When the heat treatment conditions were 750℃ / 10h + 850℃ / 5h and 750℃ / 10h + 850℃ / 10h, the prepared glass-ceramics contained both Mg₂SiO₄ and NaAlSiO₄ crystals. However, when the heat treatment conditions were 750℃ / 10h + 850℃ / 5h, the Vickers hardness of the glass-ceramic before ion exchange was relatively low. This was mainly because the second-step heat treatment time was shorter, resulting in a lower NaAlSiO₄ crystal content and a limited improvement in the bulk strength of the glass-ceramic. It was precisely because of the lower NaAlSiO₄ crystal content that the glass-ceramic exhibited a larger ion exchange layer depth. This demonstrates that the ion exchange layer depth can be controlled by adjusting the NaAlSiO₄ crystal content, thereby achieving a synergistic adjustment between the bulk strength and ion exchange performance of the glass-ceramic.
[0059] Examples 11-13 also illustrate that low-temperature heat treatment of the glass with the basic composition described in Table 2 can achieve crystallization of Mg2SiO4, while high-temperature heat treatment can achieve co-crystallization of Mg2SiO4 and NaAlSiO4. When Mg2SiO4 crystallizes alone, the glass-ceramic has a large ion exchange depth, while the crystallization of NaAlSiO4 can increase the bulk hardness of the glass-ceramic, but the ion exchange layer depth is reduced.
[0060] Table 3. Comparison of raw material formulations and results for Comparative Examples 1-7
[0061] As can be seen from Comparative Example 1 in Table 3, when the MgO content is high, due to its strong effect of promoting glass phase separation, the glass crystallizes during the casting process, making it impossible to obtain transparent original glass.
[0062] As can be seen from Comparative Example 2 in Table 3, when the content of nucleating agent TiO2 is high, its effect of promoting glass phase separation is strong, which leads to the instability of the original glass. During the casting process, the glass crystallizes and cannot obtain transparent glass.
[0063] As can be seen from Comparative Example 3 in Table 3, when the Na2O content is low, the concentration of alkali metal ions in the glass network is insufficient, and the network structure tends to be dense. This results in high viscosity and poor fluidity of the glass at 800℃, and insufficient stress relaxation ability. During the high-temperature crystallization process, it is difficult to release thermal stress and structural stress through viscous flow, thereby causing creep and warping deformation of glass products.
[0064] As can be seen from Comparative Example 4 in Table 3, when the content of nucleating agent TiO2 is low, it is difficult to form a sufficient number and uniformly distributed nucleation sites inside the glass, which leads to crystallization tending to occur preferentially from the glass surface rather than uniform bulk crystallization, ultimately resulting in deformations such as warping and collapse of the sample.
[0065] As can be seen from Comparative Example 5 in Table 3, it is difficult to form Mg2SiO4 crystals when the MgO content is low.
[0066] As can be seen from Comparative Example 6 in Table 3, when the Li2O content is high, a quartz solid solution crystal phase with a low coefficient of thermal expansion is generated. This phase does not match the thermal expansion of the Mg2SiO4 and NaAlSiO4 crystal phases with high coefficients of thermal expansion, leading to cracking after glass heat treatment.
[0067] As can be seen from Comparative Example 7 in Table 3, when the content of the nucleating agent ZrO2 is slightly high, it will induce the precipitation of other crystalline phases, and Mg2SiO4 and NaAlSiO4 crystalline phases cannot be obtained.
[0068] To fully understand the properties of the prepared glass-ceramic, samples were taken and subjected to XRD, TEM, and K-ray diffraction. + Tests on ion concentration distribution, Vickers hardness, etc., yielded the following results: Figure 1-8 As shown.
[0069] Figure 1 The images show the XRD patterns of the glass composition described in Example 8 after heat treatment under different conditions. Figure 1 It can be seen that after heat treatment at 800℃ for 10h, only Mg2SiO4 crystals precipitate in the sample; while after heat treatment at 850℃ for 10h, both Mg2SiO4 and NaAlSiO4 crystals precipitate in the sample.
[0070] Figure 2 The images show the XRD patterns of the glass composition described in Example 10 after heat treatment under different conditions. From... Figure 2 It can be seen that Mg2SiO4 and NaAlSiO4 crystals precipitate under both heat treatment conditions of 750℃ / 10h+850℃ / 5h and 750℃ / 10h+850℃ / 10h. However, when the heat treatment condition is 750℃ / 10h+850℃ / 5h, the diffraction peak intensity corresponding to NaAlSiO4 is lower, indicating that its content is low. On the other hand, when the heat treatment condition is 750℃ / 10h+850℃ / 10h, the diffraction peak intensity corresponding to NaAlSiO4 is higher, indicating that its content is higher.
[0071] Figure 3 The image shows a TEM image of a glass-ceramic formed after heat treatment at 800°C for 10 hours with the glass composition described in Example 1. The interplanar spacing in the image corresponds to the (021) crystal plane (PDF#: 74-714) of the Mg2SiO4 crystal, indicating that Mg2SiO4 crystals crystallize under these conditions.
[0072] Figure 4The image shows a TEM image of a glass-ceramic formed after heat treatment at 900°C for 10 hours with the glass composition described in Example 1. The interplanar spacing in the image corresponds to the (210) crystal plane of NaAlSiO4 (PDF#: 35-424), indicating that NaAlSiO4 crystals crystallize under these conditions.
[0073] Figure 5 The microcrystalline glass obtained by heat treatment under different conditions according to the composition of Example 8, after ion exchange at 480℃ / 8h, K + Concentration distribution curve. In the graph, "AP" represents the raw glass sheet obtained after casting, shaping, and annealing of the molten glass. From... Figure 5 It can be seen that, compared with the AP sample, the ion exchange layer depth of the sample obtained by heat treatment at 800℃ / 10h is significantly increased. (See Table 2 and...) Figure 1 It can be seen that the heat-treated sample under these conditions contains only Mg2SiO4 crystals, indicating that the crystallization of Mg2SiO4 can increase the ion exchange layer depth. However, after heat-treating the sample at 850℃ for 10h, the ion exchange layer depth decreased significantly. (See Table 2 and...) Figure 1 It can be seen that the heat-treated sample under these conditions contains both Mg2SiO4 and NaAlSiO4 crystals, indicating that the crystallization of NaAlSiO4 inhibits ion exchange.
[0074] Figure 6 The microcrystalline glass obtained by heat treatment under different conditions according to the composition of Example 10, after ion exchange at 480℃ / 8h, K + Concentration distribution curve (AP has the same meaning). From Figure 6 It can be seen that after heat treatment at 750℃ / 10h + 850℃ / 5h, the ion exchange layer depth can reach 70μm. (See Table 2 and...) Figure 2 It can be seen that the heat-treated sample under these conditions contains both Mg2SiO4 and NaAlSiO4 crystals, but the content of NaAlSiO4 crystals is low. Therefore, the depth of the ion exchange layer of the glass-ceramic remains relatively deep.
[0075] Figure 7 The images show the Vickers hardness diagrams (AP meanings are the same) of the microcrystalline glass obtained by heat treatment under different conditions before and after ion exchange, based on the composition of the glass described in Example 8. Figure 7 It can be seen that the Vickers hardness of the glass sample significantly increased after heat treatment at 800℃ for 10h. (See Table 2 and...) Figure 1 It can be seen that the glass sample after heat treatment under these conditions contains only Mg2SiO4 crystals, indicating that the crystallization of Mg2SiO4 can improve the bulk strength of the glass. When the glass sample is heat-treated at 850℃ for 10h, its Vickers hardness further increases. (See Table 2 and...) Figure 1It can be seen that the heat-treated sample under these conditions contains both Mg2SiO4 and NaAlSiO4 crystals, indicating that the crystallization of NaAlSiO4 can improve the bulk strength of the glass. From... Figure 7 It can also be seen that the Vickers hardness of the glass-ceramic was further improved after ion exchange.
[0076] Figure 8 The images show the Vickers hardness diagrams (AP meanings are the same) of the microcrystalline glass obtained by heat treatment under different conditions before and after ion exchange, based on the glass composition described in Example 10. Figure 8 It can be seen that the Vickers hardness of the glass samples significantly increased after heat treatment at 750℃ / 10h+850℃ / 5h and 750℃ / 10h+850℃ / 10h, respectively. (See Table 2 and...) Figure 2 It can be seen that the heat-treated sample under these conditions contains both Mg2SiO4 and NaAlSiO4 crystals, indicating that the crystallization of Mg2SiO4 and NaAlSiO4 can improve the bulk strength of the glass. From Figure 8 It can also be seen that the Vickers hardness of the glass-ceramic was further improved after ion exchange.
Claims
1. A high-strength microcrystalline glass, characterized in that: The high-strength microcrystalline glass comprises a glass phase and crystals dispersed in the glass phase. The crystals include crystal A, which does not contain alkali metal ions, and crystal B, which contains alkali metal ions. Crystal A is Mg2SiO4 crystal, and crystal B is NaAlSiO4 crystal.
2. The high-strength microcrystalline glass as described in claim 1, characterized in that: In the high-strength microcrystalline glass, crystal A precipitates before crystal B, and the contents of the two crystals are equal or unequal.
3. The high-strength microcrystalline glass as described in claim 1, characterized in that... The high-strength microcrystalline glass comprises the following raw materials by molar percentage: SiO2 39.7%-45.5%, MgO 31.7%-36.8%, Al2O 38.3%-14.4%, Li2O 0%-1.5%, Na2O 4.7%-8.4%, K2O 0%-1%, TiO2 3.2%-4.9%, ZrO2 0%-1%, Y2O 30%-1.5%, wherein 75.3%≤MgO+SiO2≤78.5%, 0.72≤MgO / SiO2≤1, and 0.37≤Na2O / Al2O3≤1.
02.
4. The high-strength microcrystalline glass as described in claim 1, characterized in that: The Vickers hardness of the high-strength microcrystalline glass is not less than 7.8 GPa.
5. A method for enhancing the intrinsic and overall strength of glass-ceramics using stepwise crystallization and ion exchange, characterized in that... The method includes: preparing a base glass, heat-treating the base glass to precipitate Mg2SiO4 crystals and NaAlSiO4 crystals sequentially, and performing ion exchange after heat treatment to obtain the high-strength microcrystalline glass according to any one of claims 1-4.
6. The method as described in claim 5, characterized in that... The preparation method of base glass includes: mixing base glass raw materials according to the selected ratio, then heating to 1500℃-1600℃ for melting, and after the molten glass material is formed, annealing at 600℃-650℃ to obtain base glass.
7. The method as described in claim 5, characterized in that: The base glass is heat-treated using a one-step or two-step method.
8. The method as described in claim 7, characterized in that: The one-step method includes: heat-treating the base glass at 750℃-950℃ for 5-10 hours; the two-step method includes: firstly, heat-treating the base glass at 700℃-750℃ for 5-10 hours, and secondly, transferring it to 800-950℃ for further heat treatment for 5-10 hours.
9. The method as described in claim 8, characterized in that: The base glass is heat-treated at 850℃-900℃ for 10 hours, or first heat-treated at 750℃ for 10 hours and then transferred to 850℃ for 5-10 hours.
10. The method as described in claim 5, characterized in that... The ion exchange specifically refers to K + -Na + Ion exchange was performed using KNO3 as the molten salt, at a temperature of 440℃-500℃, for a time of 2-10 hours, and with a depth of 5μm-85μm in the ion exchange layer.